Short and medium latency muscle responses evoked by electrical vestibular stimulation are a composite of all stimulus frequencies - Dakin, Christopher J.; Inglis, John Timothy; Blouin, Jean-Sébastien (Experimental brain research, 2011)
Electrical vestibular stimulation produces biphasic responses in muscles maintaining balance. The two components of these muscle responses (termed the short latency and medium latency components) are believed to be independent and elicited by vestibular stimuli of different frequencies. We tested these hypotheses by determining (a) if frequency-specific stimulation protocols could evoke independently the short and medium latency responses and (b) whether these two components are triggered by distinct brain regions with a fixed time delay, interacting around 10 Hz. First, subjects were provided 10–25 Hz, 0–10 Hz, and 0–25 Hz vestibular stimuli to selectively modulate the short latency, medium latency, or both components of the response; and second, they were provided twenty sinusoidal stimuli from 1 to 20 Hz with a 0–20 Hz control trial, designed to determine whether an interaction between the short and medium latency responses occurs at a specific stimulation frequency. Both the 0–10 Hz and 10–25 Hz vestibular stimuli elicited multiphasic waveforms, suggesting the short and medium latency components were not modulated independently by the frequency-specific stimuli. Sinusoidal vestibular stimuli evoked responses at the stimulated frequency but no evidence of a reflex component interaction was observed. Instead, summation of the responses evoked by each of the sinusoidal stimuli resembled the biphasic response to broad bandwidth stimuli. Due to the lack of interaction and linear contribution of all stimulus frequencies to both the short and medium latency responses, the present results support the use of broad bandwidth electrical vestibular signal for physiological or clinical testing.